2016
DOI: 10.1371/journal.pone.0148643
|View full text |Cite
|
Sign up to set email alerts
|

Voting Intention and Choices: Are Voters Always Rational and Deliberative?

Abstract: Human rationality–the ability to behave in order to maximize the achievement of their presumed goals (i.e., their optimal choices)–is the foundation for democracy. Research evidence has suggested that voters may not make decisions after exhaustively processing relevant information; instead, our decision-making capacity may be restricted by our own biases and the environment. In this paper, we investigate the extent to which humans in a democratic society can be rational when making decisions in a serious, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…Ben-Yashar and Zahavi (2011) present a model of committee with rational uninformed voters and study whether adding an informed voters improve the performance of the committee. However, both theoretical and empirical literature suggest that we should also consider situations where at least some agents base their votes on mistaken information (see Mandler 2012;Hayes et al 2015;Lee et al 2016). Thus, we generalize Ben-Yashar and Zahavi (2011) model in order to consider this case and study its asymptotical implications.…”
Section: Information Aggregation By a Poorly Informed Electoratementioning
confidence: 99%
“…Ben-Yashar and Zahavi (2011) present a model of committee with rational uninformed voters and study whether adding an informed voters improve the performance of the committee. However, both theoretical and empirical literature suggest that we should also consider situations where at least some agents base their votes on mistaken information (see Mandler 2012;Hayes et al 2015;Lee et al 2016). Thus, we generalize Ben-Yashar and Zahavi (2011) model in order to consider this case and study its asymptotical implications.…”
Section: Information Aggregation By a Poorly Informed Electoratementioning
confidence: 99%
“…We achieve this goal by estimating a model that compares variance explained by the paths meeting the two criteria with paths that do not. The current model is refined from previous research in evaluating the rationality of Taiwanese voters (Lee et al, 2016 ), which focused on three sets of predictors: political party preference, ethnic identification , and the voting intention of significant others . Research has identified political partisanship as one of the most robust factors in predicting voter intention and choices (e.g., Bartels, 2000 ; Hillygus and Jackman, 2003 ), both in Taiwan (Achen and Wang, 2017 ) and in other democratic societies (e.g., the U.S.; see Bartels, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The previous study, which focused on the 2014 Taipei mayoral elections, found Taiwanese voters to be largely rational (Lee et al, 2016 ). The stated party preference (i.e., explicit party preference) and an interaction between explicit and implicit party preference (i.e., subconscious, more intuitive feelings toward one party) predicted voters' intention and, in turn, their voting choices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations